New horizons in colorectal cancer surgery - Meijerink, W. J. H. J.; van der Peet, NI. H. G. M. van der Pas D. L.; Cuesta, M. A.; Meijer, S. (Revista Portuguesa de Cirurgia; No 10 (2009): Setembro 2009 - II Série, 2009)
.